Synthesis, characterization and luminescent properties of copper(I) halide complexes containing biphenyl bidentate phosphine ligand. Issue 23 (2nd December 2017) - Chen, Bu-Lin; Liu, Li; Zhong, Xin-Xin; Asiri, Abdullah M.; Alamry, Khalid A.; Li, Guang-Hua; Li, Fa-Bao; Zhu, Nian-Yong; Wong, Wai-Yeung; Qin, Hai-Mei
Abstract: Copper(I) halide complexes having thermally activated delayed fluorescence (TADF) and phosphorescence have attracted much attention. Here, a series of four-coordinate dinuclear copper(I) halide complexes, [CuX(bpbp) ]2 (bpb p = 2, 2′-bis(diphenylphosphino)biphenyl, X = I (1 ), Br (2 ) and Cl (3 )), were synthesized, and their molecular structures and photophysical properties were investigated. The structural analysis reveals that two copper(I) centers are bridged by two halogen ligands to form a dinuclear structure with a four-membered Cu2 X2 ring. These complexes exhibit yellow to blue emission in the solid state at room temperature and have peak emission wavelengths at 575–487 nm with microsecond lifetimes ( τ = 6.2–19.8 μs) and low emission quantum yields (<0.01%). The emissions of1 –3 originate from MLCT, XLCT, and IL (intraligand) transitions. Three complexes displayed good thermal stability. Abstract :